Sexual Dimorphism of New Zealand Puppet Beetles (Aderidae, Coleoptera, Tenebrionoidea): Systematic Revision, Description of Three New Genera, and Phylogeny for Zenascus, gen. n. - Grzymala, Traci L.; Leschen, Richard A.b. (Zootaxa, 2020)
The Aderidae (Coleoptera: Tenebrionoidea) of New Zeland are revised to include four genera and fourteen species. Three genera are described as new: one distributed throughout the Australasian region (Zenascus gen. n.) one endemic to the north and south islands of New Zealand (Transrenus gen. n.), and one that is endemic to the south island of New Zealand (Pseudozena gen. n.). Six species are also newly described (Pseudozena denticulata sp. n., Transrenus thulater sp. n., Zenascus roberti sp. n., Z. incensum sp. n., Z. elenae sp. n., Z. aurum sp. n.). All previously described New Zealand species of aderids contained in the preoccupied genus Xylophilus are transferred to the newly erected genus Zenascus, resulting in six new combinations (Z. antennalis (Broun), comb. n.; Z. coloratus (Broun), comb. n.; Z. luniger (Champion), comb. n.; Z. nitidus (Broun), comb. n.; Z. obscurus (Broun), comb. n.; Z. xenarthrus (Broun, 1910: 54), comb. n.). Holotype and lectotype designations are made or verified for all previously described species. The New Zealand species Xylophilus pictipes Broun is synonymized with Zenascus obscurus, syn. n. and Scraptogetus nigricans is synonymized with Scraptogetus anthracinus, syn. n. The Australian genus Pseudananca Blackburn 1893 is synonymized with the New Zealand genus Scraptogetus Broun, syn. n. Keys to the genera and species are included. Phenotypic characters previously employed in the higher classification of the Aderidae, including secondary sexually dimorphic characters, are discussed and a phylogenetic analysis for the ten New Zealand species of Zenascus is performed to reconstruct trait evolution in males, which display extreme dimorphic antennomere modifications.